GHALIZUL QALB QUR’ANIC PERPECTIVE - Purwati, Heri; Firdaus; Basri, Halimah (Jurnal Diskursus Islam, 2022)
This study is a study of ghalizul Qalb Perspectives of the Qur'an. The subject matter is "What is the essence of ghalizul qalb perspective of the Qur'an, how does ghalizul qalb of the perspective of the Qur'an look, and how a way of overcoming the hard heart of the perspective of the Qur'an. In answering this problem, this research is classified as library research using a multidisciplinary approach, including tafsir, theology, and Sufism. The Metode used in this study uses the method of interpreting mawdhu'i data collected by quoting and analyzing using content analysis (content analysis) of literature that is representative and has relevance or relation to the problem to be discussed reviews, and will conclude the results of the review. The results of this study show that (1) the term ghalizul qalb is contained in QS. Ali 'Imran/3:159, ghalizul qalb also has other terms including qasiyah (stiff heart), khatama (keyed heart), la yafqahun (incomprehensible heart), raib (doubtful heart) (2) ghalizul qalb form, i.e. explaining the kinds of hard hearts i.e., qalbun aglaf (closed heart), qalbun marid (aching heart), qalbun mushaffah (between a heart of faith and a sick heart), qalbun mankus (an upside-down heart), as for the signs of a hard heart that is, dependent on other than Allah, associates a lot with unhelpful things, always makes mistakes and always obeys the passions (3) the solution to overcome a hard heart can be done by acting meekly, to be forgiving, to restrain anger, to multiply the charity of shalih, and the muhasabah of oneself, as for the effect that after doing the methods of overcoming the hard heart, then one will gain happiness in the heart by the pleasure of looking at the face of god, longing in the world and seeing the afterlife and the benefit of the Khalik towards His being.